Canada and the League of Nations - Veatch, Richard, 1926- (Heritage., 1975)
The focus is mainly on political and security aspects of Canadian objectives and reactions but it also includes an account of a largely forgotten episoide: an appeal to the League from the Six Nation Indians against Canada.